Estudo dos polimorfismos inserção/deleção, Xba I e Eco RI no gene da apolipoproteína B e PLA1/A2 no gene da glicoproteína IIB/IIIA em pacientes jovens com acidente vascular cerebral - Caleb Guedes Miranda dos Santos (2008)
Ischemic Stroke (IS) is a multifactorial disease characterized by symptoms resulting from arterial thrombotic processes. These cases are mainly caused by atherosclerosis, a chronic inflammatory disease that results from vascular injury and lipid deposition on the wall of the arteries. This study aimed to investigate the association between the polymorphisms Xba, I, I/D and Eco RI in the apolipoprotein B and PLA1A2 of the glycoprotein GPIIb / IIIa genes and ischemic stroke in a group of young patients by means PCR/RFLP technique. We evaluated 113 patients, 48 of them from Minas Gerais State and 65 from Rio de Janeiro State. The control group was composed by 291 healthy subjects from Minas Gerais State. There was no difference between patientsfrom Minas Gerais and Rio de Janeiro when compared the frequency of each polymorphisms. However, it was observed a greater frequency of the E- mutant allele (Eco RI ) in the patients compared to the control group. The alleles X+, D, and A2 associated to predisposition to ischemic stroke showed frequencies significantly increased in patients only when the comparison was established to, at least, two polymorphism simultaneouly. In addition, presence of the allele A1 (GPIIb/IIIa), coupledto the absence of the E-mutant allele (Eco R1), showed to be strongly associated to a lower predisposition to the IS development. Thus, it can be concluded that the presence of E- mutant allele configures as a possible risk factor for development of IS.